Strategi Pengelolaan Dan Pengembangan Wisata Susur Sungai Kota Banjarmasin - Nadia Fithri, Zulfa; Riduansyah Syafari, Muhammad (Jurnal PubBis, 2025)
Regional development is crucial for national development, and one way to achieve this is through the management and development of tourism. The city of Banjarmasin is a city with significant tourism potential due to its numerous rivers that can be optimally empowered and developed. In addition to serving as a means of water transportation, these rivers are also managed as tourist attractions, such as the Banjarmasin River Cruise Tour. The purpose of this study is to analyze the management and development strategies for the River Cruise Tour in Banjarmasin using a SWOT analysis. The research method used is a mixed method, combining qualitative and quantitative research approaches. Data collection was done through interviews, observations, documentation, and questionnaires. The sampling techniques used were purposive sampling and accidental sampling, with a total of 85 respondents. The data was processed using the Internal Factor Analysis Strategy (IFAS) and External Factor Analysis Strategy (EFAS) matrices and analyzed with a SWOT analysis. The results show that the Banjarmasin River Cruise Tour has greater strengths and opportunities compared to other factors. Therefore, based on the SWOT analysis, the management and development strategy falls into Quadrant I (aggressive strategy), which is an S-O strategy. The main strategies that can be developed include leveraging collaboration by increasing partnerships with relevant stakeholders for infrastructure development and promotion, utilizing digital technology in both management and development, empowering local communities, diversifying tourism products, and introducing ecotourism to the river cruise